Fiber reinforced concrete of enhanced fire resistance for tunnel segments - Barros, Joaquim A. O. (2011)
In the last decades, technical and scientific efforts have been done to increase the concrete strength, based on the assumption that more economic, lightweight, durable and good looking structures can be built. This strength enhancement, however, has been obtained by increasing the compactness of the concrete internal structure, resulting concretes with a void percentage much lower than the values observed in concretes of current strength classes. Research and fire accidents have shown that the concrete failure of structures exposed to fire is as explosive as high is the concrete strength class, since the concrete brittleness increases with the concrete compressive strength. In the present work a fiber reinforced concrete of enhanced fire resistance was developed and its properties are characterized by experimental research. This concrete is intended to have enough resistance for the most structural engineering applications, while the performance of the fibrous reinforcement system was evaluated in terms of verifying its possibilities for replacing, partially or totally, conventional reinforcement used in concrete precast tunnel segments.